Associations between the duration of active commuting to school and academic achievement in rural Chilean adolescents (2017)
Background: Habitual active commuting to school may be positively associated with academic achievement. The aim of this study was to examine the relationship between duration of walking or otherwise actively commuting to school and academic achievement. Methods: This cross-sectional study included 389 adolescents from seven rural schools (12-13 years). Mode and duration of active commuting to school (use of active means such as walking or biking to and from school) and screen time were self-reported. Academic achievement was determined by the outcome in basic grades (language and mathematics). Results: Active commuting to school was not associated with higher scores in any grades after adjustment for potential confounders. No evidence was found of interactions between gender and academic achievement, but there was interaction with duration of walking (<30 min, 30-60 min, and >60 min). Adjusted binary logistic regression analysis suggested that adolescents who spent between 30 and 60 min actively commuting were more likely to obtain high academic achievement (language and mathematics). Conclusions: Thirty to 60 min of ACS may have a positive influence on academic achievement in adolescents, so, it is necessary to make recommendations for the children to walk from and/or to school. This could help society to recognize the relevance of physical activity to health as well as to academic performance. © The Author(s). 2017.